Transvaginal sonographic assessment of cervical length and wedging for predicting outcome of labor induction at term: a systematic review and meta‐analysis. (27th October 2013) - Verhoeven, C. J. M.; Opmeer, B. C.; Oei, S. G.; Latour, V.; van der Post, J. A. M.; Mol, B. W. J.
ABSTRACT: Objective: To perform a systematic review and meta‐analysis to assess the predictive capacity of transvaginal sonographic assessment of the cervix for the outcome of induction of labor . Methods: We searched MEDLINE, EMBASE and the Cochrane Library, and manually searched reference lists of review articles and eligible primary articles. Studies in all languages were eligible if published in full. Two reviewers independently selected studies and extracted data on study characteristics, quality and test accuracy. We then calculated pooled sensitivities and specificities (with 95% CIs) and summary receiver–operating characteristics (sROC) curves. Outcome measures were test accuracy of sonographically measured cervical length and cervical wedging for Cesarean section, not achieving vaginal delivery within 24 h and not achieving active labor . Results: We included 31 studies reporting on both cervical length and outcome of delivery. The quality of the included studies was mediocre. Sensitivity of cervical length in the prediction of Cesarean delivery ranged from 0.14 to 0.92 and specificity ranged from 0.35 to 1.00. The estimated sROC curve for cervical length indicated a limited predictive capacity in the prediction of Cesarean delivery. Summary estimates of sensitivity/specificity combinations of cervical length at different cut‐offs for Cesarean delivery were 0.82/0.34, 0.64/0.74 and 0.13/0.95 for 20, 30 and 40 mm, respectively. For cervical wedging in the prediction of failed induction of labor summary point estimates of sensitivity/specificity were 0.37/0.80 . Conclusions: Cervical length and cervical wedging as measured sonographically at or near term have moderate capacity to predict the outcome of delivery after induction of labor. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .